Common errors in organic reaction mechanisms: is there any strategy to teach students about their own errors? - Sabitu, Abdulmalik; Talib, Othman; Kamarudin, Nurzatulshima; Abdul Rahman, Norizah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Organic reaction mechanism (ORM) is the step by step sequence of elementary reactions by which overall chemical changes occurs among organic compounds in various disciplines such as agricultural science, food science, pharmacy, medicine and other life sciences. The concept has been perceived as difficult by many students and therefore learned it by memorisation which resulted to partial recall and misconceptions that accumulated to errors of serious concern. An understanding of students’ errors could be valuable as acquiring an insight and having the knowledge about it makes changes possible to decrease it negative consequences in the future. Hence, teachers were saddle with the responsibity of recognizing students’ errors as an important part of promoting students learning and deeper understanding. However, the way chemistry teachers manages students’ errors in ORM have been localised and may differ between teachers across institutions and among countries. Hence, this study is aimed at reviewing literature on students’ common errors in ORM to find out the strategy used for teaching students about their own errors. Scoping method was employed to select and extensively review past researches selected based on key variable of organic reaction mechanisms, students errors, Delphi methods and error correction theory (Repair Learning Theory) from researches conducted and published in databases including web of science, science direct and Emerald between the period of 2010 to 2018. It was found that there was no common strategy for teaching students about their own errors instead teachers try to either avoid the errors or reduced it based on their own experiences. Delphi method as an alternative communication tool for achieving consensus amongst experts and practitioners can be used to get agreement among chemistry teachers strategies used in overcoming students errors in ORM. Based on the nature of students’ common errors and the Delphi method, it was recommended that when students’ common errors are known, their causes can be identified and hence development of a common error strategy (CErS-ORM) for teaching ORM was proposed. Theories such as Repair Learning Theory, would be a fruitful pursuit to theorize the strategy developed for simplifying learning organic reaction mechanisms and help students to avoid errors in the future.